Keabsahan Pengelolaan Keuangan Desa - Heri Santoso (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
This research aimed to discuss the substance of the financial management in the village, the legality of evidence administrative Village Budget (APBDes) and determine the legal basis for the financial management in the village. This research used qualitative descriptive approach. Informants in this study consisted of village head, village secretary, village officials, Rural Community Empowerment Agency (LPMD) and Village Consultative agency (BPD), as well as society in Sidoarjo Regency. These Results from this study were first, namely the preparation of village revenue sources in APBDes into three groups: Revenue Village, transfers and other revenues. Second, common irregularities in a village financial management included financing and spending beyond that is set of APBDes and illegal of payment proof that is made by treasurer. It is aimed to keep orderly bookkeeping. Financial management will be better when supported by the accounting records and supporting evidence properly.